1. The problem statement, all variables and given/known data Use the IMPLICIT FUNCTION THEOREM (and not implicit diﬀerentiation) to ﬁnd dy/dx at the point (1,1) when y^5 + x^2*y^3 − y*e^(x^2) = 1. 2. Relevant equations f(x,y)=0 dy/dx = - [f(x)/f(y)] = -[d/dx(f(x,y) / d/dy(f(x,y)] 3. The attempt at a solution solving for f(x,y), i brought the 1 to the left side so the equation equaled 0, i.e y^5 + x^2*y^3 − y*e^(x^2)-1=0 then d/dx of the function I got 2xy^3 - 2xye^(x^2) d/dy = 5y^4 + 3x^2y^2 - e^(x^2) so dy/dx was just -[d/dx / d/dy] = -[2xy^3 - 2xye^(x^2) / 5y^4 + 3x^2y^2 - e^(x^2)] for the point (1,1) i just plugged in x and y into the above equation, and got 0.65 as my answer.